Maternal employment and childhood overweight in Germany - Sophie-Charlotte Meyer (University of Wuppertal, Schumpeter School of Business and Economics, 2015)
A widespread finding among studies from the US and the UK is that maternal employment is correlated with an increased risk of child overweight, even in a causal manner, whereas studies from European countries obtain less conclusive results. As evidence for Germany is still scarce, the purpose of this study is to identify the effect of maternal employment on childhood overweight in Germany using two sets of representative micro data. Moreover, we explore potential underlying mechanisms that might explain this relationship. In order to address the selection into maternal full-time employment, we use an instrumental variable strategy exploiting the number of younger siblings in the household as an instrument. While the OLS model suggests that maternal full-time employment is related to a 5 percentage point higher probability of the child to be overweight, IV estimates indicate a 25 percentage points higher overweight probability due to maternal full-time employment. Exploring various possible pathways, we find that maternal employment is associated with unhealthy dietary and activity habits which might explain the positive effect of maternal employment on child overweight to some extent. Several sensitivity analyses confirm the robustness of our findings.
urn:nbn:de:hbz:468-20150617-090621-8
Keywords: I12; J22; J13; 330; maternal employment; childhood overweight; BMI; maternal labor supply